2019
DOI: 10.1021/acsinfecdis.8b00284
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic Gold(III) Complex [Au(Hdamp)(L14)]+ (L1 = SNS-Donating Thiosemicarbazone) as a Candidate to New Formulations against Chagas Disease

Abstract: Chagas disease remains a serious public health concern with unsatisfactory treatment outcomes due to strain-specific drug resistance and various side effects. To identify new therapeutic drugs against Trypanosoma cruzi, we evaluated both the in vitro and in vivo activity of the organometallic gold­(III) complex [Au­(III)­(Hdamp)­(L14)]Cl (L1 = SNS-donating thiosemicarbazone), henceforth denoted 4-Cl. Our results demonstrated that 4-Cl was more effective than benznidazole (Bz) in eliminating both the extracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 49 publications
0
9
0
1
Order By: Relevance
“…Fexinidazole, an NTR-1-activated 5-nitroimidazole pro-drug [ 31 ], has been shown to outperform both benznidazole and nifurtimox as a curative treatment for experimental T. cruzi infections [ 34 ] ( Figure 2 A,B, as example), and a clinical trial to assess efficacy and tolerability against patients with asymptomatic chronic infections has been undertaken [ 35 ]. In addition, there have also been a number of recent studies reporting encouraging preliminary data on the antiparasite activities of other novel nitroaromatics [ 88 ], and of a new generation of diverse organometallic compounds [ 89 , 90 , 91 , 92 ].…”
Section: Progress In Chagas Disease Drug Developmentmentioning
confidence: 99%
“…Fexinidazole, an NTR-1-activated 5-nitroimidazole pro-drug [ 31 ], has been shown to outperform both benznidazole and nifurtimox as a curative treatment for experimental T. cruzi infections [ 34 ] ( Figure 2 A,B, as example), and a clinical trial to assess efficacy and tolerability against patients with asymptomatic chronic infections has been undertaken [ 35 ]. In addition, there have also been a number of recent studies reporting encouraging preliminary data on the antiparasite activities of other novel nitroaromatics [ 88 ], and of a new generation of diverse organometallic compounds [ 89 , 90 , 91 , 92 ].…”
Section: Progress In Chagas Disease Drug Developmentmentioning
confidence: 99%
“…The increased lipophilicity after complexation enhances their cellular uptake, but also decreases their solubility in aqueous media, which is a serious drawback in terms of bioavailability, and can in worst case distort the obtained in vitro results. We came across such an effect when we re‐evaluated some of the previously determined in vitro parameters of the non‐halogenated complex 4‐H . Actually, we found that the previously determined CC 50 value for this compound was too high, most probably due to an insufficient solubility at higher concentrations.…”
Section: Resultsmentioning
confidence: 94%
“…Lopes and co‐workers showed the effective activity of the non ‐ halogenated [Au(dampH)(L‐H)]Cl . It eliminates both the extracellular trypomastigote and the intracellular amastigote forms of the parasite.…”
Section: Resultsmentioning
confidence: 99%
“…Intermolecular interactions of the best poses were analyzed by using the LigPlot software [23] with the conformational structures presented with PyMOL. The methodologies of the theoretical studies of molecular modeling performed here are similar in manner to previous works [24][25][26][27].…”
Section: Docking Calculations -Compound -Receptor Protocolmentioning
confidence: 99%